Quality and methods of developing practice guidelines - Clark Otavio; Marshburn Jan; Winiarek Magdalena; Cruse Hugh; Djulbegovic Benjamin (BMC, 2002)
Abstract Background It is not known whether there are differences in the quality and recommendations between evidence-based (EB) and consensus-based (CB) guidelines. We used breast cancer guidelines as a case study to assess for these differences. Methods Five different instruments to evaluate the quality of guidelines were identified by a literature search. We also searched MEDLINE and the Internet to locate 8 breast cancer guidelines. These guidelines were classified in three categories: evidence based, consensus based and consensus based with no explicit consideration of evidence (CB-EB). Each guideline was evaluated by three of the authors using each of the instruments. For each guideline we assessed the agreement among 14 decision points which were selected from the NCCN (National Cancer Comprehensive Network) guidelines algorithm. For each decision point we recorded the level of the quality of the information used to support it. A regression analysis was performed to assess if the percentage of high quality evidence used in the guidelines development was related to the overall quality of the guidelines. Results Three guidelines were classified as EB, three as CB-EB and two as CB. The EB guidelines scored better than CB, with the CB-EB scoring in the middle among all instruments for guidelines quality assessment. No major disagreement in recommendations was detected among the guidelines regardless of the method used for development, but the EB guidelines had a better agreement with the benchmark guideline for any decision point. When the source of evidence used to support decision were of high quality, we found a higher level of full agreement among the guidelines' recommendations. Up to 94% of variation in the quality score among guidelines could be explained by the quality of evidence used for guidelines development. Conclusion EB guidelines have a better quality than CB guidelines and CB-EB guidelines. Explicit use of high quality evidence can lead to a better agreement among recommendations. However, no major disagreement among guidelines was noted regardless of the method for their development.